Effects of ovarian phase on oocyte quality in cows (Bangladesh Veterinarian, 2024)
The effect of ovarian phase on oocyte quality in slaughterhouse material of cows was studied. Cumulus-oocyte complexes (COCs) were aspirated from all visible follicles. COCs were graded on the number and intensity of the cumulus cells and the homogeneity of the ooplasm as A (4 – 5 layers compact cumulus with a homogeneous ooplasm), B (1 - 2 layers compact cumulus with homogeneous ooplasm having a coarse appearance), C (slightly expanded cumulus with irregular cluster ooplasm), and D (denuded oocyte or expanded cumulus, irregular ooplasm). The overall aspiration rate of COCs was 37.2%. The aspiration rate was significantly higher (P